1998
DOI: 10.1111/j.1651-2227.1998.tb01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Foetal supraventricular tachycardia treated with sotalol

Abstract: Sonesson S‐E, Fouron J‐C, Wesslen‐Eriksson E, Jaeggi E, Winberg P. Foetal supraventricular tachycardia treated with sotalol. Acta Pædiatr 1998; 87: 584‐7. Stockholm. ISSN 0803‐5253 This retrospective study (1991‐95) presents our experience with sotalol in the treatment of 14 foetuses with supraventricular tachycardia (SVT). SVT was diagnosed in a structurally normal heart at a gestational age of 24‐35 (median 28) weeks. In eight foetuses, hydrops was evident at presentation. In all patients pharmacological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…24 When these drugs were used as first choice, termination of AF/SVT before birth occurred in 51% of fetuses (115 of 226) with digoxin, 6 -9,13,14,19,20,25 in 64% (45 of 70) with flecainide, 4,6 -8,16 and in 66% (23 of 35) with sotalol. 10,12,15,19 This implies that sotalol and flecainide may be the most effective drugs regardless of the underlying arrhythmia mechanism. Nevertheless, clinically more relevant than rates of arrhythmia termination at birth is the response time to a particular intervention, and this information is available only for digoxin in 1 study.…”
Section: First-line Medicationmentioning
confidence: 99%
“…24 When these drugs were used as first choice, termination of AF/SVT before birth occurred in 51% of fetuses (115 of 226) with digoxin, 6 -9,13,14,19,20,25 in 64% (45 of 70) with flecainide, 4,6 -8,16 and in 66% (23 of 35) with sotalol. 10,12,15,19 This implies that sotalol and flecainide may be the most effective drugs regardless of the underlying arrhythmia mechanism. Nevertheless, clinically more relevant than rates of arrhythmia termination at birth is the response time to a particular intervention, and this information is available only for digoxin in 1 study.…”
Section: First-line Medicationmentioning
confidence: 99%
“…Sotalol has been used as a second-line agent to treat fetal supraventricular tachycardia (SVT) with mixed results. [1][2][3][4][5] In 2000, Oudijk et al 2 reported discouraging results with sotalol in the treatment of fetal SVT because of the high fetal mortality associated with treatment. However, 3 of the 4 nonsurviving fetuses were grossly hydropic at presentation, a factor that likely contributed to their death.…”
mentioning
confidence: 99%
“…[9] Sotalol, a beta adrenergic antagonist, has been recently introduced in the treatment of SVT in fetuses with and without fetal hydrops. [4] Potential pro-arrhythmic effects of sotalol remain a source of concern, which excludes it as the drug of Þ rst choice in uncomplicated SVT. In cases with severe hydrops and poor cardiac function, due to its possible negative inotropic effect, the drug should always be administered in association with digoxin.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] Other agents such as flecainide and sotalol have been tried as first-line agents but with adverse events. [3,4] We report a case of fetal supraventricular tachyarrhythmia with hydrops detected at 32 weeks and managed with combination of oral digoxin and sotalol.…”
Section: Introductionmentioning
confidence: 99%